Miracle Reports and the Argument from Analogy - Keener, Craig S. 1960- (2015)
Traditionally, scholars used the argument from historical analogy to deny the historical reliability of extraordinary miracle claims in the Gospels, claims such as visible healings, instant cures of blindness or inability to walk, resuscitations from death, and nature miracles. In view of a wide body of global reports available today, the analogy argument instead supports the historical plausibility of eyewitness reports of these experiences.